Іван Петрович Білокінь (до 90-річчя від дня народження) - Kudrenko, І.К. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
In the article is dedicated to 90 anniversary of birth of Ivan Petrovich Belokon’ elucidate his life way, scientific and organization activities. Conducted analysis scientific legacy of this scientist.